Osteoarthritis and Sleep: The Johnston County Osteoarthritis Project - ALLEN, KELLI D. (J Rheumatol, 2008)
OBJECTIVE: Little is known about the association of symptomatic osteoarthritis (OA) with sleep disturbance. We compared the prevalence and severity of current sleep problems among individuals with and without symptomatic hip or knee OA in a large, community-based sample. METHODS: Participants (N = 2682, 28% with symptomatic hip or knee OA) were from the Johnston County Osteoarthritis Project. Six sleep variables were grouped into 2 categories: insomnia (trouble falling asleep, trouble staying asleep, or waking early) and insufficient sleep (daytime sleepiness, not enough sleep, or not feeling rested). The presence of any sleep problem (insomnia or insufficient sleep) was also assessed, as were annual frequency and cumulative days of sleep problems. Adjusted models examined associations of symptomatic OA with sleep problems controlling for demographic characteristics, obesity, self-reported health, and depressive symptoms. RESULTS: Symptomatic hip or knee OA was associated with increased odds of any sleep problem (odds ratio 1.25, 95% confidence interval 1.02–1.54), insomnia (OR 1.29, 95% CI 1.07–1.56), and insufficient sleep (OR 1.35, 95% CI 1.12–1.62) in adjusted models. Among participants with sleep problems, those with symptomatic OA reported higher median numbers of annual and cumulative days of insomnia and insufficient sleep, although these associations were not statistically significant in adjusted models. CONCLUSION: Symptomatic hip and knee OA are significantly associated with sleep problems, independent of other factors related to sleep difficulties, including self-rated health and depression. Patients with OA should be regularly screened for sleep disturbance as part of routine care. (J Rheumatol First Release May 15 2008)